Effect of different fish cooking method on plasma lipid levels healthy young adults in Kendari, Southeast Sulawesi - Farida (2023)
Some nutrients contained in fish, particularly unsaturated fatty acid, have atheroprotective effect by lowering on total cholesterol, triglyceride, and Low Density Lipoprotein (LDL),and increasing High Density Lipoprotein (HDL). Quantities of fatty acid vary considerably by cooking and preservation methods. Cooking and preservation methods is important to be considered because some methods of cooking can alter nutrition profiles, particularly fatty acid profiles. The aim of this study was to evaluate the different fish cooking method on blood lipid levels. Cooking method was measured by Semiquantitative Food Frequency Questionnaire (SQFFQ). Subject was interviewed about their fish cooking habits in a last month. Plasma lipid concentrations were measured enzimatically by Cholesterol Oxidase-Peroxidase Aminoantipyrine Phenol (CHOD-PAP) method. There was no different statistically (p>0.005) on plasma lipid levels (triglycerides, total cholesterol, LDL, and HDL) between fried and nonfried fish consumption. No significance correlation between cooking method and plasma lipid levels. Different fish cooking method was not affect the plasma lipid levels. Total fish intake was more dominant than cooking method to affect the plasma lipid. Consuming fried fish with no flour layered, and not using hydrogenated oil may give beneficial effect on plasma lipid.